NCOG-24. TIME TO FIRST RECURRENCE AND SURVIVAL IN IDH-WILDTYPE GLIOBLASTOMA. (14th November 2022) - Pan, Peter; Joanta-Gomez, Adela; Yuen, Carlen; Donovan, Laura; Haggiagi, Aya; Welch, Mary; Iwamoto, Fabio; Lassman, Andrew
Abstract: INTRODUCTION: Time to recurrence is a source of considerable anxiety in glioblastoma. Assuming survival to a certain timepoint without tumor progression, how do odds/outcomes change relative to initial starting conditions? Is there a single timepoint with highest risk of tumor progression, after which "the longer you go, the longer you go"? METHODS: Newly-diagnosed glioblastomas were retrospectively reviewed (n=209). Pre-2012 diagnoses (n=2) & IDH-mutants excluded (n=8). Median PFS/OS and remaining time to mPFS were calculated for sub-populations without disease progression (POD) at 0, 3, 6, 8, 12, and 24 months post-surgery. RESULTS: 199 IDH-wildtype glioblastomas identified -- 40% women, median age 63 years (range 26-91), 43% gross-total resection, 65% MGMT unmethylated, 65% upfront RT 60Gy (23% 40Gy) -- mPFS 8 months / mOS 19 months. Patients without POD within 3 months had mOS 20 months. Outcomes progressively improve at later timepoints-- mPFS 10/13/20/39 months and mOS 23/27/39/65 months, for patients without POD at 6/8/12/24 months post-surgery respectively. Patients without POD at 24 months comprised 10% of original cohort (n=20; 8 deaths). As a surrogate for risk of tumor progression, remaining time to mPFS was calculated (taken as difference between timepoint in question, and mPFS for the population of patients without POD up to that timepoint) and followed a J-shape curve -- 8 months (at 0 months post-surgery), 4 months (for patients without POD at 6 months post-surgery), 7-8 months (for patients without POD at 10-14 months post-surgery), to 13 and 15 months (for patients without POD at 18 and 24 months post-surgery, respectively). DISCUSSION: Sub-populations without early progression appear to have improved survival relative to baseline, which has implications for clinical trials without internal controls. Nevertheless, highest risk for tumor progression seems to be at 6 months post-surgery, after which it appears "the longer you go, the longer you go."